Edukasi kesehatan tentang mobilisasi dini dan kegawatdaruratan post sectio caesarea: SIGAP IBU (Siap, Gerak Aktif Ibu) - Irisanna Tambunan; Tuti Suprapti; Raden Siti Jundiah; Ade Iwan Mutiudin; Raihany Sholihatul Mukaromah (JOURNAL of Public Health Concerns, 2026)
Background: Caesarean section (CS) is an obstetric procedure whose use is increasing in Indonesia, even exceeding the WHO recommendation (10–15%). This increasing prevalence of cesarean sections raises the risk of postoperative complications. Early mobilization after a cesarean section is an intervention proven effective in accelerating the recovery process, preventing complications, improving blood circulation, reducing pain, and improving organ function. Ongoing education is needed to ensure mothers are truly capable of correctly performing early mobilization independently. Early mobilization practices still face obstacles, primarily due to mothers' lack of knowledge, fear of pain, and minimal support from health workers and families. Purpose: To improve the knowledge and skills of cadres regarding early mobilization, wound care, and early detection of emergency first aid signs in post-cesarean section mothers. Method: The community service activity was carried out on November 13, 2025, in the RW PKK Anyelir 12 Cikutra area. Thirteen mothers, including cadres of the integrated health post (Posyandu) and integrated health post (Poswindu), were involved as respondents, assisted by two university students, and attended by health workers assigned to the local area. The activity was carried out by delivering material covering wound care management for post-cesarean section mothers, post-cesarean section care, and early detection of emergency signs of first aid for post-cesarean section mothers, accompanied by simulations and demonstrations. Knowledge levels were assessed using questionnaires administered before and after the educational activity (pre-test) and after the educational activity (post-test). Evaluation was carried out through observation during the simulation and to see the results of the activity by comparing changes in pre-test and post-test scores. The results of the activity were presented descriptively to illustrate the increase in respondents' knowledge and skills. Results: Shows that the level of knowledge of respondents before educational activities was 3 (23.1%) and the good category and 10 (76.9%) in the less category, while after educational activities it became 12 (92.3%) in the good category and 1 (7.7%) in the less category. Based on the questionnaire scores also showed that the average knowledge score of respondents before educational activities was 63 points and after educational activities it became 81 points. Conclusion: Systematic education and training activities on early mobilization using a demonstration approach have proven effective in improving the abilities and skills of health cadres. There has been an increase in understanding, mindset, attitudes, and behavior regarding early mobilization and early detection of emergency first aid signs for post-cesarean sections. Suggestion: It is hoped that the sustainability of the program can be monitored through communication with the cadre mothers, using communication media and directly. This activity is also expected to be implemented routinely and periodically in integrated health post (Posyandu) activities so that understanding of early mobilization can benefit the wider community. Keywords: Cadres; Early mobilization; Emergency; Health education; Sectio caesarea Pendahuluan: Sectio caesarea (SC) merupakan salah satu tindakan obstetri yang semakin meningkat penggunaannya di Indonesia, bahkan sudah melebihi angka rekomendasi WHO (10–15%). Peningkatan prevalensi sectio caesarea ini menimbulkan risiko komplikasi pasca operasi. Mobilisasi dini pasca sectio caesarea merupakan salah satu intervensi yang terbukti efektif dalam mempercepat proses pemulihan, mencegah komplikasi, memperlancar peredaran darah, mengurangi nyeri, dan memperbaiki fungsi organ. Perlunya edukasi berkelanjutan agar ibu benar-benar mampu melaksanakan mobilisasi dini secara mandiri dengan benar. Praktik mobilisasi dini masih menghadapi kendala, terutama karena kurangnya pengetahuan ibu, ketakutan terhadap nyeri, serta minimnya dukungan dari tenaga kesehatan dan keluarga. Tujuan: Untuk meningkatkan pengetahuan dan ketrampilan kader tentang mobilisasi dini, perawatan luka dan deteksi dini tanda-tanda kegawatdaruratan pertolongan pertama pada ibu post sectio caesarea. Metode: Kegiatan pengabdian dilaksanakan pada tanggal 13 november 2025, di wilayah RW PKK Anyelir 12 Cikutra. Melibatkan 13 ibu kader posyandu dan poswindu untuk menjadi responden dan dibantu 2 mahasiswa serta dihadiri tenaga kesehatan yang bertugas di wilayah setempat. Kegiatan dilaksanakan dengan penyampaian materi meliputi manajemen perawatan luka pada ibu post sectio caesarea, perawatan pada ibu post sectio caesarea dan deteksi dini tanda-tanda kegawatdaruratan pertolongan pertama pada ibu post sectio caesarea yang disertai simulasi dan demonstrasi. Penilaian tingkat pengetahuan menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Evaluasi dilakukan dengan observasi ketika melakukan simulasi dan untuk melihat hasil kegiatan dengan membandingkan perubahan nilai pre-test dengan post-test. Hasil kegiatan disampaikan secara deskriptif untuk menggambarkan peningkatan pengetahuan dan keterampilan responden. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum kegiatan edukasi adalah sebanyak 3 (23.1%) dan kategori baik dan sebanyak 10 (76.9%) dalam kategori kurang, sedangkan setelah kegiatan edukasi menjadi sebanyak 12 (92.3%) dalam kategori baik dan sebanyak 1 (7.7%) dalam kategori kurang. Berdasarkan dari skor kuesioner juga menunjukkan bahwa rata-rata skor pengetahuan responden sebelum kegiatan edukasi adalah 63 poin dan sesudah kegiatan edukasi menjadi 81 poin. Simpulan: Kegiatan edukasi dan pelatihan yang sistematis mengenai mobilisasi dini dengan pendekatan demonstrasi terbukti efektif meningkatkan kemampuan dan ketrampilan kader kesehatan. Terdapat peningkatan pemahaman, pola pikir, sikap dan perilaku tentang mobilisasi dini dan deteksi dini tanda-tanda kegawatdaruratan pertolongan pertama pada ibu post sectio caesarea. Saran: Diharapkan untuk keberlanjutan program dapat dipantau melalui komunikasi dengan ibu-ibu kader menggunakan media komunikasi maupun secara langsung. Kegiatan ini diharapkan juga untuk diaplikasikan secara rutin dan berkala dalam kegiatan posyandu agar pemahaman tentang mobilisasi dini dapat bermanfaat kepada masyarakat yang lebih luas